2008
DOI: 10.2114/jpa2.27.33
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Force Tremor on Mechanomyographic Signals Recorded with an Accelerometer and a Condenser Microphone during Measurement of Agonist and Antagonist Muscles in Voluntary Submaximal Isometric Contractions

Abstract: The purpose of this study was to investigate the influence of force tremor (FT) on the mechanomyogram (MMG) recorded by a condenser microphone (MIC) and an accelerometer (ACC) for the measurement of agonist and antagonist muscles during submaximal isometric contractions. Following determination of the isometric maximum voluntary contraction (MVC), 10 male subjects were asked to perform elbow flexion and extension at 20%, 40%, 60%, and 80% MVC. Surface electromyogram (EMG) and MMG of the biceps brachii (BB) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In other words, Flexion and Extension show a similar connectivity topology, and Pronation and Supination present the same phenomena. This could be a result of the fact that MMG captures not only the contraction of the agonist muscles but also the relaxation of the antagonist muscles, both simultaneously occurring during the task and found to be present at low frequencies [62]. Interestingly, similar topologies were found between Extension and Pronation across all frequency components for each amputee participant.…”
Section: B Muscle Connectivity Networkmentioning
confidence: 80%
“…In other words, Flexion and Extension show a similar connectivity topology, and Pronation and Supination present the same phenomena. This could be a result of the fact that MMG captures not only the contraction of the agonist muscles but also the relaxation of the antagonist muscles, both simultaneously occurring during the task and found to be present at low frequencies [62]. Interestingly, similar topologies were found between Extension and Pronation across all frequency components for each amputee participant.…”
Section: B Muscle Connectivity Networkmentioning
confidence: 80%
“…2) Force and Torque Evaluation: Three studies [31], [34], [87] were associated with force in MMG signals (Table VI). Dillon et al [34], for example, investigated MMG RMS amplitudes and MPF versus isometric force relationships detected from the RF muscle using a laser displacement sensor in the perpendicular and transverse axes.…”
Section: Muscle Characterizations Using Mmg 1) Fatigue and Strengtmentioning
confidence: 99%
“…Further, Youn et al [31] demonstrated the feasibility of using MMG signals to estimate the isometric elbow flexion force for the BB and brachioradialis (BRD) muscles based on an artificial neural network. In another work, Kim et al [87] discussed the influence of force tremor on MMG signals recorded by an accelerometer and a microphone in the measurement of agonist and antagonist muscles during voluntary sub-maximal isometric contractions.…”
Section: Muscle Characterizations Using Mmg 1) Fatigue and Strengtmentioning
confidence: 99%
“…The cylindrical hole through the PCB acted as a hollow chamber between the microphone diaphragm and the skin surface. This setup is shown in Fig 2A and is similar to the one shown in Kim et al [19]. An IMU (Model: LSM9DS0, STMicroelectronics, Geneva, Switzerland) was placed over microphone unit #8, which was positioned over the middle of exterior wrist, or, in other words, at the top of the entire sensor arrangement over the wrist, as illustrated in Fig 1. Our prototype utilized only one IMU to record limb movement and it was not in skin contact with the wrist.…”
Section: Introductionmentioning
confidence: 99%